Gambaran Status Identitas Remaja di Persekutuan Remaja Gereja "F" - Rindorindo, Adely; Purwanti, Margaretha (MANASA, 2025)
Adolescence is a crucial phase for identity formation, requiring proper guidance to avoid confusion or inappropriate development. The Youth Fellowship at Church "F" seeks to assess the identity status of adolescents they mentor to create tailored programs. This study used a descriptive quantitative approach with 40 participants aged 13-16 from the fellowship. Data were collected using The Revised Objective Measure of Ego Identity Status, validated for reliability and contextual relevance. The study revealed that none of the adolescents had achieved identity achievement status. Most were in the diffusion status for both ideological (career, religion, politics, and philosophy) and interpersonal (friendships, partnerships, gender roles, and recreation) aspects. Adolescents in this status showed limited desire to explore or commit to these areas. Additionally, some adolescents were in foreclosure status, characterized by identity development shaped by external influences like parents or schools without personal exploration. The findings highlight the importance of mentors addressing the needs of adolescents at all identity statuses. Special attention is recommended for those in foreclosure status, as their identity development may lack the autonomy required for healthy growth. Tailored mentoring programs should encourage exploration and self-discovery to support identity development effectively. These results provide valuable insights for designing programs that cater to the unique developmental needs of adolescents in the Youth Fellowship at Church "F."